Peran Apresiasi Sastra dalam Mengembangkan Kemampuan Berbahasa Anak Sekolah Dasar - Markus Sampe (FKIP UNSULTRA, 2025)
Literary appreciation is an activity that involves understanding, interpreting, and experiencing literary works by readers. At the elementary school level, literary appreciation not only introduces children to a variety of literary texts, but also makes a significant contribution to the development of language skills, both oral and written. This article is a literature study that aims to examine various research results and theories related to the role of literary appreciation in developing elementary school children's language skills. The results of the study show that literary appreciation activities such as reading aloud, storytelling, role-playing, and rewriting stories can improve listening, speaking, reading, and writing skills. Children's literature that is rich in vocabulary, varied sentence structures, and cultural values ​​is an effective means of strengthening children's linguistic abilities holistically. In addition, this activity also fosters interest in reading and forms critical and imaginative thinking skills. This study recommends that teachers in elementary schools consistently integrate literary appreciation in Indonesian language learning as a contextual, communicative, and enjoyable approach.